Transport simulations of the pre–thermal–quench phase in ASDEX Upgrade massive gas injection experiments. (15th January 2016) - Fable, E.; Pautasso, G.; Lehnen, M.; Dux, R.; Bernert, M.; Mlynek, A.
Abstract: The pre–thermal–quench (PTQ) phase of the massive gas injection (MGI) scenario to terminate the tokamak plasma discharge is studied by means of one-dimensional (1D) transport simulations. This phase is characterized by the cold–front penetration in the hot plasma after the gas has been released from the valves, and before the actual thermal quench takes place, with consequent plasma disruption at lower stored energy. The comparison between the simulations and the ASDEX Upgrade (AUG) experiments allows to gain insight in the observed dependencies and time scales. Despite the genuine three-dimensional structure of the problem, it is shown that the 1D simulations are already giving experimentally relevant answers, the reason for which will be discussed in detail. Influence of unknown parameters and simplifying assumptions are also discussed.